Performance of the Trioplex real-time RT-PCR assay for detection of Zika, dengue, and chikungunya viruses - Gilberto A. Santiago (Nature Portfolio, 2018)
The Trioplex real-time RT-PCR assay was developed for detection of Zika virus infections in areas with dengue and chikungunya transmission. Here, Santiago et al. describe the optimization and clinical performance of the assay, showing high sensitivity for detection and differentiation of the three viruses.